2008
DOI: 10.1002/ange.200704758
|View full text |Cite
|
Sign up to set email alerts
|

Highly Regio‐, Diastereo‐, and Enantioselective [2+2+2] Cycloaddition of 1,6‐Enynes with Electron‐Deficient Ketones Catalyzed by a Cationic RhI/H8‐binap Complex

Abstract: Zwei quartäre Kohlenstoffzentren entstehen bei der im Titel genannten Bildung von anellierten Dihydropyranen (siehe Schema). Der gleiche Katalysator vermittelt auch die ortho‐Funktionalisierung von Arylketonen mit 1,6‐Eninen mit ausgezeichneter Regio‐ und Enantioselektivität. Z=Amid, C(CO2Me)2, O; E=CO2Et, Ac; R1=Me, Aryl, CO2Me; R2=Me; R3=Me, CO2Et.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The reaction exhibits complete formation was reported by Tanaka and co-workers in 2008 using (R)-H 8 -BINAP as the chiral ligand. 94 In 1994, Kim and co-workers described a Rh-catalyzed alkylation of 2-phenylpyridines with olefins (Scheme 49). 95 The linear products were predominately obtained, suggesting a Rh−H involved mechanism.…”
Section: Alkylation Via C−h Activation 21 Alkylation Of Aromatic C−h ...mentioning
confidence: 99%
“…The reaction exhibits complete formation was reported by Tanaka and co-workers in 2008 using (R)-H 8 -BINAP as the chiral ligand. 94 In 1994, Kim and co-workers described a Rh-catalyzed alkylation of 2-phenylpyridines with olefins (Scheme 49). 95 The linear products were predominately obtained, suggesting a Rh−H involved mechanism.…”
Section: Alkylation Via C−h Activation 21 Alkylation Of Aromatic C−h ...mentioning
confidence: 99%
“…141 Under related conditions, in this case using either (R)-H 8 -BINAP or (R)-BINAP, three examples of aromatic ketone functionalization were described by Tanaka et al, also proceeding with high levels of enantiocontrol (94−98% ee). 142 Selected examples from Shibata's study include benzophenonederived 178a and (E)-chalcone-derived 178b. Shibata and coworkers proposed that the reaction begins with a directed oxidative addition of Rh into the proximate C(sp 2 181, which reductively eliminates to release the desired products…”
Section: C(sp 2 )−H Functionalizationmentioning
confidence: 99%
“…[3] Although there are several reports on transition-metal-catalyzed cyclization of allenyl aldehydes, [1][2][3][4] only one example of [2+2+2] cycloaddition [5] of allenyl aldehydes with CÀC multiple bonds has been reported to date. [6][7][8] Very recently, Tanaka and co-workers reported a Rh I -catalyzed enantioselective [2+2+2] cycloaddition of allenyl aldehydes with internal alkynes (Scheme 1). [6] They reported that tosylamidelinked allenyl aldehydes afforded [2+2+2] cycloaddition products in moderate yields (28-50 %) with good to high enantioselectivity (34-99 % ee), although malonate-linked allenyl aldehydes are not applicable for this cycloaddition (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%